Hubungan Kepercayaan Diri dan Kecemasan Terhadap Keterampilan Dasar Ekstrakurikuler Futsal Siswa SD Al Amanah - Najib Ilham Najmudin; Indra Safari; Dewi Susilawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the level of relationship between self-confidence with basic skills and anxiety towards basic futsal skills of students aged 10-12 years. The study used a quantitative method with a correlational design on 30 students aged 10-12 years who were in the futsal extracurricular at Al-Amanah Elementary School, with a purposive sampling technique. The instruments used were A Short Instrument for Measuring Students Confidence with Key Skills (SICKS) , Sport Anxiety Scale-2 (SAS-2) , and the Basic Futsal Skills Test Model for KU Players 10-12 Years. The results showed that the level of confidence was in the very high category with a percentage of 47%. The level of anxiety was in the very low category with a percentage of 53%, and basic futsal skills were in the medium category with a percentage of 47%. The Spearman correlation test showed a significant positive relationship between self-confidence and basic skills (r = 0.686). While anxiety with basic skills showed a significant negative relationship (r = -0.405). It was concluded that increased self-confidence correlated positively with basic skills, while anxiety correlated negatively with basic skills. These findings indicate that self-confidence and anxiety can influence basic futsal skills in elementary school age. The researchers hope this study can provide guidance for coaches and parents so that students can demonstrate their potential. Keywords: Self-Confidence, Anxiety, Basic Futsal Skills, Students Aged 10-12 Years